Prospective motion correction enables highest resolution time‐of‐flight angiography at 7T. Issue 1 (11th December 2017) - Mattern, Hendrik; Sciarra, Alessandro; Godenschweger, Frank; Stucht, Daniel; Lüsebrink, Falk; Rose, Georg; Speck, Oliver
Abstract : Purpose: Higher magnetic field strengths enable time‐of‐flight (TOF) angiography with higher resolution to depict small‐vessel pathologies. However, this potential is limited by the subject's ability to remain motionless. Even small‐scale, involuntary motion can degrade vessel depiction, thus limiting the effective resolution. The aim of this study was to overcome this resolution limit by deploying prospectively motion‐corrected (PMC) TOF. Methods: An optical, marker‐based, in‐bore tracking system was used to update the imaging volume prospectively according to the subject's head motion. PMC TOF was evaluated in 12 healthy, cooperative subjects at isotropic resolution of up to 150 μm. Image quality was assessed qualitatively through reader rating and quantitatively with the average edge‐strength metric. Results: PMC significantly increased the average edge strength and qualitatively improved the vessel depiction in nine out of 11 cases. Image quality was never degraded by motion correction. PMC also enabled acquisition of the highest resolution human brain in vivo TOF angiography to date. Conclusion: With PMC enabled, high‐resolution TOF is able to visualize brain vasculature beyond the effective resolution limit. Magn Reson Med 80:248–258, 2018. © 2017 International Society for Magnetic Resonance in Medicine.